2022
DOI: 10.3389/fvets.2021.795947
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Radiographic Measurements in Ferrets Using the OsiriX MD Programme

Abstract: Objectives: To adapt the vertebral heart scale (VHS) for use in ferrets and identify new scales and tools that allow to establish the normal heart size by means of radiography more quickly and effectively.Methods: Forty healthy pet ferrets (Mustela putorius furo) were used in this prospective study. The measurements were made on right lateral, left lateral, ventrodorsal, and dorsoventral projections, using OsiriX MD medical imaging software, to evaluate sex effect and variance within the different heart scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…. 10 They found that RL‐VHS was significantly different between 21 males and 19 females whereas VD‐VHS was not 10 . The influence of weight and sex on heart size indicators normalized for body size remains unclear in ferrets in the light of current literature.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…. 10 They found that RL‐VHS was significantly different between 21 males and 19 females whereas VD‐VHS was not 10 . The influence of weight and sex on heart size indicators normalized for body size remains unclear in ferrets in the light of current literature.…”
Section: Discussionmentioning
confidence: 97%
“…Gutiérrez et al. concluded similarly between RL‐VHS and LL‐VHS 10 . However, they stipulated that VD‐VHS and DV‐VHS measurements behaved differently and showed perceptible differences that could be valuable.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations